50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-399
|View full text |Cite
|
Sign up to set email alerts
|

On Heatshield Shapes for Mars Entry Capsules

Abstract: The 70° sphere-cone -the standard geometry for all US Mars entry missions -is thoroughly examined via flow field simulations at a select few peak heating points along candidate flight trajectories. Emphasis is placed on turbulent heating based on the BaldwinLomax turbulence model. It is shown that increased leeward turbulent heating for a 70° sphere-cone flying at angle of attack is primarily due to the discontinuity in curvature between the spherical nose cap and the conical frustum -the attachment of the son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The study presented in this paper considers a single geometry (shown in Fig. 3) based on previous missions and numerical investigations [23,50]. The vehicle shape is representative of a generic hypersonic re-entry geometry, a 30…”
Section: Resultsmentioning
confidence: 99%
“…The study presented in this paper considers a single geometry (shown in Fig. 3) based on previous missions and numerical investigations [23,50]. The vehicle shape is representative of a generic hypersonic re-entry geometry, a 30…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the eliminating the discontinuity in curvature between the nose cap and cone frustum results in a favorable pressure gradient over the entire lee-side (when flown at an angle of attack similar to MSL), and avoids increased turbulent heating due to the sonic line attachment at the cap/cone junction. 9) Based on data on similar spherical aeroshell capsule shapes, a series of ballistic coefficients were selected for analysis in the current study (see Table 2). The corresponding entry mass at Mars (based on a nominal hypersonic drag coefficient of 1.46) is also shown.…”
Section: Aeroshellmentioning
confidence: 99%
“…Atmospheric entry refers to the movement of human made or natural objects as they enter the atmospheric of a planet from outer space, in the case of Earth from an altitude above the "edge of space" [2]. The vehicle which enters into the atmospheric conditions from the outer space is known as Entry Vehicle.…”
Section: Introductionmentioning
confidence: 99%